Giant neurofibroma around the knee in a 34-year-old male: a case report - Kumar, Chandan; Mishra, Amrita (International Surgery Journal, 2026)
Neurofibromatosis type 1 (NF1) is an autosomal dominant genetic disorder characterized by multiple neurofibromas, café-au-lait macules, and skeletal abnormalities. Plexiform neurofibromas can attain large sizes, causing functional impairment and cosmetic deformity. Surgical excision remains the primary treatment for symptomatic lesions. A 34-year-old male with a known history of NF1 presented to the General Surgery OPD with a progressively enlarging mass around the left knee and multiple swellings over the body for 15 years. The swelling around left knee was associated with discomfort during walking and restriction of knee movements. Physical examination revealed a large, soft-to-firm, non-tender mass measuring approximately 10×12 cm involving the anterior aspect of the knee. Magnetic resonance imaging (MRI) of left knee suggested a large soft tissue mass consistent with neurofibroma without intra-articular extension. CECT Chest suggested few apical bullas and multiple cutaneous fibromas. The patient underwent complete surgical excision of the mass under general anaesthesia. Histopathological examination confirmed the diagnosis of neurofibroma. The postoperative period was uneventful, and the patient showed significant functional improvement during follow-up. Giant neurofibromas around the knee are uncommon and can significantly impair mobility. Early diagnosis and complete surgical excision can provide symptomatic relief, improve function, and prevent further complications.